1986
DOI: 10.3189/s0022143000012132
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth in Polar Ice: II. Application

Abstract: ABSTRACT. Grain growth observed in polar ice that is not deforming rapidly can be accounted for if concentrations and distributions of extrinsic materials (microparticles, bubbles, and dissolved impurities) are characterized fully. Dissolved impurities segregate to grain boundaries and slow grain growth in all cold glacial ice. The high concentration of soluble impurities in Wisconsinan ice from the Dome C (Antarctica) ice core (and perhaps other ice cores) probably causes the small grain-sizes observed in tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 35 publications
(86 reference statements)
1
53
1
8
Order By: Relevance
“…Although the detailed estimates of ice grain size in clean and dirty ice vary from core to core (clean, interglacial ice has d $ 0.8 to 4 mm, whereas dusty, cloudy, glacial ice has d $ 0.6 to 3.5 mm); within each core, grains in impurity-laden ice are invariably smaller than those in clean ice. These values lend support to the ''rule of thumb'' within the glacial community that ice that looks dirty, cloudy, or bubbly has smaller grains than ice that looks clear and clean [Alley et al, 1986a[Alley et al, , 1986b.…”
Section: Effect Of Impuritiessupporting
confidence: 59%
“…Although the detailed estimates of ice grain size in clean and dirty ice vary from core to core (clean, interglacial ice has d $ 0.8 to 4 mm, whereas dusty, cloudy, glacial ice has d $ 0.6 to 3.5 mm); within each core, grains in impurity-laden ice are invariably smaller than those in clean ice. These values lend support to the ''rule of thumb'' within the glacial community that ice that looks dirty, cloudy, or bubbly has smaller grains than ice that looks clear and clean [Alley et al, 1986a[Alley et al, , 1986b.…”
Section: Effect Of Impuritiessupporting
confidence: 59%
“…The drag effects of impurities, discussed below, thus appear to be a and concluded that the dust concentration in polar ice cores was too low to have a significant effect on grain growth rates. On the other hand,Alley et al [1986b] concluded that higher concentrations of soluble impurities, mainly chloride and sulphate, in Wisconsin ice from the Dome C ice core slowed the migration of grain boundaries and thereby reduced grain growth rates. variations in the core can be assumed to mirror those in dust quite closely.…”
mentioning
confidence: 99%
“…During this open system refreezing, most of the gases remain dissolved into the water reservoir, although the TGC of DRL is slightly higher (2-6 mL gas kg −1 ice , Fig. 2c of small crystals reflects the inhibition of their normal grain growth from the presence of debris (Alley et al, 1986). While the melting-refreezing DRL have to be formed at the ice-sediment interface, several processes have been proposed to explain their occurrence higher up in the basal ice sequence.…”
Section: A Scenario For the Build-up Of The Neem Basal Ice Sequencementioning
confidence: 99%